A Stable Homoleptic Divinyl Tetrelene Series. Issue 33 (14th May 2021) - Roy, Matthew M. D.; Baird, Samuel R.; Dornsiepen, Eike; Paul, Lucas A.; Miao, Linkun; Ferguson, Michael J.; Zhou, Yuqiao; Siewert, Inke; Rivard, Eric
Abstract: The synthesis of the new bulky vinyllithium reagent ( Me IPr=CH)Li, ( Me IPr=[(MeCNDipp)2 C]; Dipp=2, 6‐ i Pr2 C6 H3 ) is reported. This vinyllithium precursor was found to act as a general source of the anionic 2σ, 2π‐electron donor ligand [ Me IPr=CH] − . Furthermore, a high‐yielding route to the degradation‐resistant Si II precursor Me IPr⋅SiBr2 is presented. The efficacy of ( Me IPr=CH)Li in synthesis was demonstrated by the generation of a complete inorganic divinyltetrelene series ( Me IPrCH)2 E: (E=Si to Pb). ( Me IPrCH)2 Si: represents the first two‐coordinate acyclic silylene not bound by heteroatom donors, with dual electrophilic and nucleophilic character at the Si II center noted. Cyclic voltammetry shows this electron‐rich silylene to be a potent reducing agent, rivalling the reducing power of the 19‐electron complex cobaltocene (Cp2 Co). Abstract : Silylene? NHO Problem ! Access to a new lithiated anionic N‐heterocyclic olefin (NHO) yields a complete acyclic divinyltetrelene series.